The Role of Intestinal Stem Cells in Epithelial Regeneration Following Radiation-Induced Gut Injury - Kim, Chang-Kyung (Curr Stem Cell Rep, 2017)
PURPOSE OF REVIEW: Intestinal epithelial cells show remarkable plasticity in regenerating the epithelium following radiation injury. In this review, we explore the regenerative capacity and mechanisms of various populations of intestinal stem cells (ISCs) in response to ionizing radiation. RECENT FINDINGS: Ionizing radiation targets mitotic cells that include “active” ISCs and progenitor cells. Lineage-tracing experiments showed that several different cell types identified by a single or combination of markers are capable of regenerating the epithelium, confirming that ISCs exhibit a high degree of plasticity. However, the identities of the contributing cells marked by various markers require further validation. SUMMARY: Following radiation injury, quiescent and/or radioresistant cells become active stem cells to regenerate the epithelium. Looking forward, understanding the mechanisms by which ISCs govern tissue regeneration is crucial to determine therapeutic approaches to promote intestinal epithelial regeneration following injury.